Grammarly adoption among higher-education students in Yogyakarta - Amali, Muhammad Thoyib (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
Education has experienced significant changes due to recent advances in information technology. Technological developments, such as Grammarly, are pivotal in enhancing language education, benefiting learners of English as a Second Language. This research's primary objective is to examine the impact of online ad exposure and reference groups on the adoption of Grammarly while considering trust as the mediating role. This research utilized a quantitative approach by surveying 120 higher-education students in Yogyakarta. The analysis technique used in this research is path analysis using the SmartPLS program. Based on hypothesis testing, online ad exposure and reference groups have a positive and significant impact on Grammarly adoption behavior, where trust takes the role of full mediation on the relationship between online ad exposure and adoption behavior. Meanwhile, trust serves as partial mediation in the relationship between reference groups and adoption behavior. Furthermore, the managerial implications the researcher can suggest for Grammarly are to improve the performance of the features offered further, where improvements to the feedback provided by Grammarly should be more contextual and relevant.